Prevalence and associated factors of depression and posttraumatic stress disorder among trauma patients: multi-centered cross-sectional study - Gebresenbet, Eden Alemayehu; Zegeye, Samson; Biratu, Tolesa Diriba (Frontiers in Psychiatry, 2025)
BackgroundStress-related disorders, such as post-traumatic stress disorder (PTSD), are expected to be the leading cause of global mortality and morbidity by 2030. However, there is limited information on the prevalence of depression and PTSD among trauma patients in Ethiopia. Our study was aimed at determining the prevalence of depression and PTSD and factors affecting it among trauma patients.MethodsA hospital-based, multi-centered, cross-sectional study was conducted among 621 patients who visited the trauma outpatient clinic from April to June 2023. The stratified random sampling technique was used to select participants. Data were collected using standardized and pretested structured questionnaires and face-to-face interviews. Post-traumatic stress disorder was measured by the posttraumatic stress disorder checklist for DSM-5 (PCL-5), and depression was assessed by the Patient Health Questionnaire (PHQ-9). Data were analyzed using STATA version 14.1. Bivariable and multivariable logistic regression models were used to examine the association between outcome and independent variables. P-values less than 0.05 were considered statistically significant.ResultsIn this study, 621 study participants were involved, with a response rate of 100%. More than half (55%) of the participants were male. The participants’ median age was 32 years, and the interquartile range (IQR) ranged from 25 to 43 years. The prevalence of depression was 35.4% (95% CI: 31.65–39.2), and the prevalence of PTSD was 14.2% (95% CI: 11.4–16.9). In multivariable analysis, being female (AOR = 1.58, 95% CI: 1.05-2.35), having no formal education (AOR = 1.7, 95% CI: 1.01- 2.85), having a low income (AOR = 4.5, 95% CI: 1.93-10.70), and having poor social Support (AOR=2.04, 95% CI 1.34-3.10) and multiple traumatic events (AOR=7.2, 95% CI: 4.1-12.7) were significant predictors of depression. For post-traumatic stress disorder, being female (AOR=2.7, 95% CI 1.46-5.06), no formal education (AOR=2.61, 95% CI: 1.25-5.46), urban residency (AOR=2.11, 95% CI: 1.14-3.90), having depression (AOR=7.01, 95% CI: 3.65-13.46), and multiple traumatic events (AOR=8.08, 95% CI: 2.83-23.14) were the associated factors identified.Conclusion and recommendationThe study revealed high levels of depression and post- traumatic stress disorder among trauma patients. Targeted interventions addressing socio-demographic disparities, such as income and education levels, alongside psychosocial support, are imperative.